Does intraoperative reduction result in better outcomes in low-grade lumbar spondylolisthesis after transforaminal lumbar interbody fusion? A systematic review and meta-analysis - Qin, Rongqing; Zhu, Min; Zhou, Pin; Guan, Anhong (Frontiers in Medicine, 2024)
The study aimed to compare the clinical efficacy and safety of reduction versus arthrodesis in situ with transforaminal lumbar interbody fusion (TLIF) for low-grade lumbar spondylolisthesis. Study design: Systematic review and meta-analysis. Methods: A comprehensive literature retrieval was implemented in Pubmed, Embase and Cochrane library. Randomized or non-randomized controlled trials published up to July 2023 which compared reduction versus arthrodesis in situ with minimally invasive or open-TLIF for low-grade spondylolisthesis were achieved. Quality of included studies were evaluated by the Newcastle-Ottawa Scale (NOS). Data were extracted according to the predefined outcome measures, including operation time and intraoperative blood loss; short and long-time follow-up of VAS back pain (VAS-BP) and Oswestry Disability Index (ODI); spippage and segmental lordosis; the complication and fusion rate. Results: Five studies (n=495 patients) were finally included. All of them were retrospective cohort studies with Evidence Level Ⅱ. The pooled data revealed that both techniques had similar patient-reported outcomes (VAS, ODI, Good and excellent rate) during short and long-term follow-up. And no significant difference was observed in the fusion and complication rate. However, although reduction group did achieve better slippage correction, it was associated with more operation time and intraoperative blood loss comparing with arthrodesis in situ group. Conclusions: Based on the available evidence, intraoperative reduction does not result in better clinical outcomes in low-grade spondylolisthesis after minimally invasive or open-TLIF, and arthrodesis in situ technique could be an alternative.